Optical Properties of Mn2+ Doped ZnS Nanoparticles - Pathak, C.S.; Mandal, M.K. (Asian Journal of Chemistry, 2011)
Mn2+ doped ZnS nanoparticles have been synthesized by chemical precipitation method at room temperature. During synthesis process a stabilizing agent EDTA has been used to study its effect on the particle size of the synthesized material. The morphology of the prepared Mn2+ doped ZnS nanoparticles have been characterized by using X-ray diffraction and scanning electron microscope. The optical properties of the synthesized Mn2+ doped ZnS nanoparticles have been done using UV-VIS spectrophotometer and photoluminescence using F-2500 FL spectrophotometer. The size of the particle when EDTA is not used as a stabilizer is found to be 5.52 nm and when EDTA used as a stabilizer the particle size is reduced to 4.77 nm. The value of the band gap energy estimated from spectrophotometer data has been found to be in range of 3.85- 4.36 eV. Room temperature photoluminescence spectrum shows that the Mn2+ doped sample exhibits a yellow emission peak at 575 nm.